Use of a Smartphone for Improved Self-Management of Pulmonary Rehabilitation - A. Marshall; O. Medvedev; A. Antonov (International Journal of Telemedicine and Applications)
Patients suffering from chronic respiratory disease need to follow a rehabilitative exercise programme, in order to self-manage their illness and improve quality of life. Adherence to the programme is highly dependent on professional support from a physiotherapist and hence declines when patients seek to self-manage in the home. A number of requirements were identified for a Smartphone-based application in which patients are supported remotely and given automatic feedback during exercise. An application is described which will improve adherence during pulmonary rehabilitation.